ANALISIS GAYA KEPEMIMPINAN KEPALA SEKOLAH DI SMP NEGERI 6 RAMBAH SAMO KABUPATEN ROKAN HULU - Zikri; Hadriana; Sumarno (Laboratorium Program Studi Pendidikan Guru Sekolah Dasar, 2021)
As an organization, every school faces external constraints that affect the implementation of its activities, creating a dynamic and complex environment that brings uncertainty and challenges for principals in directing the institution toward its goals. The leadership style of the principal is a crucial factor influencing school success. This study aimed to describe and analyze the leadership style of the principal at SMP Negeri 6 Rambah Samo, Kabupaten Rokan Hulu, as well as the factors influencing it. A qualitative method was employed, with data collected through in-depth interviews, observation, and documentation, and analyzed using source, method, and theory triangulation. The results indicated that the principal applied leadership styles including encouraging subordinate initiatives, imposing sanctions, awarding achievements, and conducting work meetings; however, improvements were needed in decision-making, communication, task delegation, and supervision of task implementation.